Application of passive sampling (CHEMCATCHER) technique in monitoring heavy metals of lead (Pb) and chromium (Cr) in a metalic recycling industry at Binh yen, Nam Dinh, Vietnam - Dao Duy Nam (College of Engineering, University of the Philippines Diliman, 2013)
This study aims to investigate the adsorption mechanism of heavy metals using a passive sampling technique, referred to as Chemcatcher, as applied in the monitoring of contaminated water systems. A Chemcatcher is basically a Chelating Empore disk as a TM receiving phase overlaid a cellulose acetate membrane. The study is conducted in two (2) parts. The first part of the study is a calibration stage wherein adsorption behavior of the Chemcatcher with individual concentrations of Pb and Cr and their Pb-Cr interactions are investigated under controlled-tank conditions in aqueous environment. Sampling rate of the device defined as the equivalent volume of water extracted per unit time (Rs, L.h-1), which is affected by water flow rate, temperature and turbulence. The second part assessed the performance of Chemcatcher as applied to actual monitoring of surface water at an aluminum recycling industry at Binh Yen village, Nam Dinh, Vietnam. The performance of Chemcatcher is compared to the result of the conventional spot monitoring sampling technique within a 72 hours field deployment at two (2) predetermined sampling sites. The result of the calibration stage showed that sampling rates are in the range of .0082 to 0.024 L.h-1 for Pb, and 0.0025 to 0.0042 Lh-1 for Cr. Increasing the water temperature resulted in increased sampling rates. However, the corresponding increase in sampling rates is negligible when concentration of Pb and Cr concentrations are higher. Values of sampling rates of Pb and Cr are decreased when Pb and Cr are combined in solution compare with the individual solutions of Pb and Cr. Adsorption and accumulation behaviors of Pb and Cr onto Chemcatcher follow the Fick's first law in aqueous environment. In the field application, the Pb and Cr concentrations in the Chemcatcher are significantly lower compared to those exhibited in the analysis of Pb and Cr concentrations using the conventional spot water samples collected over the same period. This means that the concentration of heavy metals that can be explained by the behavior of this sampler that measures only the labile fraction of Pb and Cr in water. Nevertheless, concentration of heavy metals by Chemcatcher samples as known understanding clearly of bioavailable and bioaccumulation and toxicity of heavy metals.